Analysis of the Distribution Model of Productive Zakat Assets at LAZISMU Bojonegoro from the Perspective of Indonesian Council of Ulama Fatwa No. 14 of 2011: Analisis Model Distribusi Zakat Aset Kelolaan Pada Lazismu Bojonegoro Perspektif Fatwa Mui No. 14 Tahun 2011 - Seftia Rahmawati; Muttaqin Choiri (Program Studi Hukum Ekonomi Syari'ah, 2026)
To increase the economic independence of mustahik, this program utilizes zakat funds to support productive businesses. Fatwa No. 14 of 2011, supports the productive distribution of zakat, as done by the ChickenMu program. To make zakat more effective in reducing poverty and improving people's welfare, this fatwa also considers socio-economic dynamics. This study aims to analyze the suitability of the implementation of zakat distribution in the form of managed assets in the ChickenMu Program of Lazismu Bojonegoro with MUI Fatwa No. 14 of 2011. This research uses a descriptive method with a qualitative approach, which is based on the provisions of Islamic law and MUI fatwa, to examine the legality and implementation of productive zakat distribution.The research was conducted at the Bojonegoro Lazismu office, East Java, focusing on the ChickenMu business unit which manages zakat assets in the form of business equipment. The results showed that, ChickenMu Program of Lazismu Bojonegoro applies zakat distribution in the form of managed assets in accordance with MUI Fatwa No. MUI No. 14 of 2011 concerning the distribution of zakat assets in the form of managed assets. This program adopts the concept of productive zakat to empower mustahik towards economic independence.